Studi Formulasi, Stabilitas dan Efektivitas Gel Hand Sanitizer Ekstrak Etanol 80% Akar Kayu Kuning (Arcangelisia flava (L.) Merr.) - Dyera Forestryana; Selfira Hidayah; Revita Saputri; Hafiz Ramadhan (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
Hand sanitizer gel is a practical preparation method for hand sanitizers. Repeated use of hand sanitizers with chemical antiseptics can cause irritation and dry skin, so natural antiseptics could be used as an alternative to overcome these problems. Akar Kuning contains berberine alkaloid compounds, flavonoids, saponins, and terpenoids, which possess antibacterial properties. This study aims to develop a gel hand sanitizer for Akar Kuning with various gelling agents. Evaluation of the formula included organoleptic, homogeneity, pH, viscosity, spreadability, adhesion, hedonic test, and freeze-thaw stability. The effectiveness of the gel preparation was measured using the replica method. The results showed that the ethanolic extract of Akar Kuning contains alkaloids, flavonoids, tannins, saponins, and terpenoids. Based on the ANOVA analysis (sig < 0.05), there were significant differences in the characteristics of gel hand sanitizers. The stability test showed that formula one and formula. Three formulas were stable based on the analysis of the paired sample t-test. The optimal formula for hand sanitizer gel with 80% ethanol extract of Akar Kuning is formula one, which has an effect of 40.33% to reduce the number of bacteria.